States, agency, and power on the ‘peripheries': exploring the archaeology of the later Iron Age societies in precolonial Mberengwa, CE 1300-1600s - Nyamushosho, Robert Tendai (Department of Archaeology, 2021)
In southern Africa, as elsewhere, the tendency of Iron Age (CE 200-1900) researchers has been to focus on the more prominent places on the landscape, especially those believed by pioneering archaeologists to have been centres of big states. Consequently, most research foci were accorded to Mapungubwe, Great Zimbabwe, Khami, Danamombe and many other places considered as centres (mizinda) of expansive territorial states. However, landscapes away from, and in-between these states and their centres are traditionally viewed as ‘peripheries' where resources that made them prosperous were extracted. The inhabitants of such ‘peripheries' are presented as if they possessed little or no agency. One such area is Mberengwa, a gold-rich area situated between the edges of Mapela, Mapungubwe, Great Zimbabwe, Danamombe, and Khami. This thesis explores the archaeology of Chumnungwa, a drystone-walled muzinda located in Mberengwa. Because of abundant gold, and a landscape optimal for cattle production and crop agriculture, Chumnungwa is often marginalised as a docile ‘periphery' of the more powerful and territorial states that surrounded it. Stratigraphic excavations were performed in different parts of the site to recover artefactual and chronological evidence. Indications are that the inhabitants of Chumnungwa exploited locally acquired resources such as gold, iron, and soapstone, but mixed these with resources from distant areas. Cumulatively, this evidence, when assessed in relation to chronology, suggests that Chumnungwa flourished more or less at the same time as Mapela, and the later phases of Mapungubwe, Great Zimbabwe, Khami, and Danamombe. As a powerful actor in Mberengwa, Chumnungwa also networked and was therefore entangled not only with local, but also with regional, and inter-regional politicoeconomic processes. This suggests it is only a historical invention that can marginalise some landscapes as ‘peripheral', especially in the absence of research, but once attention is directed to them, multiple layers of agency and entanglement emerge.